MULTIVARIATE CALIBRATION TECHNIQUE FOR THE SPECTROPHOTOMETRIC QUANTIFICATION OF IVERMECTIN IN PHARMACEUTICAL FORMULATION - S, MADHAN; J, KAVITHA; KS, LAKSHMI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present abstract makes the use of multivariate calibration technique for the quantification of ivermectin in pharmaceutical dosage form. Methods: Multivariate calibration technique is based on the use of linear regression equations, by correlating the relation between concentration and absorbance at seven different selected wavelengths. The λmax of ivermectin was found to be 245 nm. The results were treated statistically. This statistical approach gives optimum results by eliminating the fluctuations arising from the instrumental or experimental conditions. Results: The developed method was validated as per the ICH guidelines and was found to be simple, linear, accurate, precise, and reproducible. The method was found to be linear over a concentration range of 5–15 μg/mL with a correlation coefficient (r2) value of about 0.9998. The limit of detection and quantification were found to be 0.029 and 0.087 μg/mL, respectively. The percentage relative standard deviation for intraday and interday precision was found to be in the range of 0.473–1.373 and 0.301–1.617, respectively. The percentage recovery was found within the range of 97.60–101.80% w/w. Conclusion: The results evidence that a simple, linear, precise, accurate, sensitive, and reproducible multivariate calibration technique has been developed and validated for the quantification of ivermectin in bulk and pharmaceutical formulation.